Factors influence entrepreneurship among Muslim fisheries community in Kedah - Shafrizan, Abdul Hamid (2022)
Fishermen are a minority group working at sea. Fishermen are often associated as the poor who have to deal with their problems with low incomes. Poverty of fishermen is a complex problem of life and it is very important to be seriously considered by various parties. Therefore, there are also fishermen who venture as entrepreneurs. These fishermen entrepreneurs have a positive attitude to earn side income. Next, the entrepreneur processes the raw materials from the catch into products for sale. The production of products by fishermen entrepreneurs is taking a new step as it helps the government in the economy. This study uses a qualitative method. Eight informants consisting of fishermen entrepreneurs from the category of coastal fishermen or zone A fishermen were interviewed to obtain data for this study. The collected data were analyzed using thematic analysis methods. The findings of the study show that there are several factors that influence the fishermen community among them to become an entrepreneur. The factors that can explain the results of the study are the factors of attitude, thought and behavioral. Therefore, this study is expected to contribute to a better understanding of the factors influence entrepreneurship among Muslim fisheries community in Kedah. This study is also expected to provide real exposure by fishermen entrepreneurs and also guidance to the relevant parties to help fishermen entrepreneurs in the future.